Incremental Principal Component Pursuit for Video Background Modeling - Rodríguez, P.; Wohlberg, B. (Springer Science and Business Media, LLC, 2016)
Video background modeling is an important preprocessing step in many video analysis systems. Principal component pursuit (PCP), which is currently considered to be the state-of-the-art method for this problem, has a high computational cost, and processes a large number of video frames at a time, resulting in high memory usage and constraining the applicability of this method to streaming video. In this paper, we propose a novel fully incremental PCP algorithm for video background modeling. It processes one frame at a time, obtaining similar results to standard batch PCP algorithms, while being able to adapt to changes in the background. It has an extremely low memory footprint, and a computational complexity that allows real-time processing.
Keywords: Principal component pursuit; Video background modeling; Incremental singular value decomposition; https://purl.org/pe-repo/ocde/ford#1.02.00